Penilaian Postur Kerja di Area Konstruksi CV. Valasindo dengan Metode Quick Exposure Check - Fita Permata Sari; Bambang Suhardi; Rahmaniyah Dwi Astuti (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2017)
CV. Valasindo is a furniture industry where the production process is still done manually. In the construction area, the operator have to work with static posture as well as gain exposure of vibrations caused from the machine that is being operated. It is feared to affect the health and safety of workers. Work posture assessment is done to determine whether the workstations in the construction area need to be improved. Work posture assessment is carried out using Quick Exposure Check. This method was chosen because it is simple and also considers observer and worker’s point of view. Quick Exposure Check also considers other factors such as vibration, the perceived difficulties of workers, and the stress level. Based on the results, all the work stations in construction area are on the range of exposure level 59%-70%. It means that all the workstations need an improvement in any time soon